2013
DOI: 10.1145/2450142.2450146
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of conservative valued CSPs

Abstract: We study the complexity of valued constraint satisfaction problems (VCSP). A problem from VCSP is characterised by a constraint language, a fixed set of cost functions over a finite domain. An instance of the problem is specified by a sum of cost functions from the language and the goal is to minimise the sum. Under the unique games conjecture, the approximability of finite-valued VCSPs is wellunderstood, see Raghavendra [FOCS'08]. However, there is no characterisation of finite-valued VCSPs, let alone general… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(125 citation statements)
references
References 71 publications
1
124
0
Order By: Relevance
“…finitevalued languages [35]. Informally, the difficulty can be attributed to the fact that tractable finite-valued languages are characterized by fractional polymorphisms with an arbitrarily large support (if the size of the domain is not fixed), whereas for conservative languages we need two fractional polymorphisms that contain a constant number of operations in the support, namely 2 and 3 [24].…”
Section: Our Resultsmentioning
confidence: 99%
“…finitevalued languages [35]. Informally, the difficulty can be attributed to the fact that tractable finite-valued languages are characterized by fractional polymorphisms with an arbitrarily large support (if the size of the domain is not fixed), whereas for conservative languages we need two fractional polymorphisms that contain a constant number of operations in the support, namely 2 and 3 [24].…”
Section: Our Resultsmentioning
confidence: 99%
“…By [19] if follows from Claims 2 and 3 that Γ admits a conservative ternary multimorphism Mj 1 , Mj 2 , Mn 3 such that for every {x, y} ∈ M , Mj 1 , Mj 2 , Mn 3 restricted to {x, y} is an MJN, which finishes the proof of Proposition 42.…”
Section: Claimmentioning
confidence: 56%
“…The proof of the other implication consists of a sequence of claims and heavily relies on the results of [19].…”
Section: Conservative Languagesmentioning
confidence: 99%
“…In ref. 1 it is shown that distinguishing between the possibilities reduces to deciding whether a certain finite system (based on A) has a property called "balance"-a problem that is known (5) to be decidableand to deciding whether A has an algebraic invariant called an STP-MJN multimorphism (6). This can be checked by brute force, given A.…”
Section: The Problem and What Is Knownmentioning
confidence: 99%